The Effect of Using an Animation Video in Writing Recount Text at SMK Antartika 1 Sidoarjo - Eka Nofa Ayu Istiqomah (International Consortium of Education and Culture Research Studies, 2021)
The objectives of this research are to find out whether there is any effect and significant difference achievement of students in writing recount text between before and after being taught by using an animation video and how the students’ respon toward the use of an animation video in teaching writing recount text. The research was conducted at SMK Antartika 1 Sidoarjo. Sample of this study is students in first grade TPM 6 class. The method that is used in this research is quantitative method with pre-experimental design. To get the data, the researcher gave pre-test and post-test to the students. The researcher used an animation video in teaching writing recount text. An essay is given by the researcher to the students to know the effect of the students after used an animation video. Based on the result of the research, there are some research findings that can be represented. First, there is significant difference achievement of students in writing recount text. Second, the students’ understanding give a positive respon toward the use of an animation video. In conclusion, the use of holiday animation video gives a significant difference on the students’ achievement in writing recount text and the students’ respon of the use of an animation video in teaching writing recount text are positive.